2014
DOI: 10.5830/cvja-2014-011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of Ankaferd blood stopper on the prevention of postoperative pericardial adhesions : cardiovascular topic

Abstract: SummaryObjectivesAnkaferd has been used as a blood-stopping agent and it may also have an anti-inflammatory effect. We investigated the efficacy of Ankaferd in preventing postoperative pericardial adhesions in an experimental rabbit model.MethodsSixteen New Zealand white rabbits were used and categorised into two groups: an Ankaferd and a control group. The Ankaferd group of rabbits was treated with a sponge impregnated with Ankaferd solution, which was applied over the abraded epicardium. A sponge impregnated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…According to several previous studies, although the mechanism of adhesion formation is not fully understood, fibroblast activity and inflammatory responses are believed to be important in the pathogenesis of adhesion formation (23). The most significant histopathological finding observed in the surgical field is excessive fibroblast migration, which causes scarring and fibrosis (11,16).…”
Section: █ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several previous studies, although the mechanism of adhesion formation is not fully understood, fibroblast activity and inflammatory responses are believed to be important in the pathogenesis of adhesion formation (23). The most significant histopathological finding observed in the surgical field is excessive fibroblast migration, which causes scarring and fibrosis (11,16).…”
Section: █ Resultsmentioning
confidence: 99%
“…Conversely, Behcet et al showed that ABS was not efficient in reducing postoperative intra-abdominal adhesions, with the degree of fibrosis and fibroblast amount increasing with the dosage of ABS (1). Nazli et al showed that topical application of Ankaferd could increase pericardial adhesion after abrasive injury of the epicardial surface in an experimental rabbit model (23).…”
Section: █ Resultsmentioning
confidence: 99%
“…A post-mortem histopathological examination revealed a hepatic venous outfl ow obstruction, indicating a potential life-threatening effect of even a small amount of the drug. Nazlı et al applied ABS-soaked sponges over the abraded epicardium of 16 white rabbits to test whether ABS prevents post-operative pericardial adhesions (15) . The authors reported that ABS did not prevent the adhesions but caused the formation of pericardial adhesions and fi brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Acta Cirúrgica Brasileira -Vol. 30 (12) experimental peripheral nerve injuries model, and it was showed that the stereological analysis techniques can supply correct and trustworthy estimates of fibroblast count and epidural fibrosis [15][16] .…”
Section: The Effects Of Ankaferd Blood Stopper and Microporous Polysamentioning
confidence: 99%
“…İlaç AS, Istanbul, Turkey) is a folkloric medicinal plant extract product, which has historically been used in Turkish practical medicine as a hemostatic agent [26][27][28][29][30] . It is a standardized mixture of the agent containing various ratios of five herbal extracts: Thymus vulgaris, Glycyrrhiza Glabra, Vitis Vinifera, Alpinia Officinarum, and Urtica Dioica.…”
Section: Ankaferd Blood Stopper ® (Abs) (Trend Teknolojimentioning
confidence: 99%